2018
DOI: 10.1155/2018/2376240
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Outcomes of Temporal Zone II-Sparing Laser Photocoagulation Combined with Intravitreal Bevacizumab in Retinopathy of Prematurity

Abstract: Background/Aim The aim of the study was to investigate the outcomes of temporal Zone II-sparing laser photocoagulation combined with intravitreal bevacizumab (IVB) in patients with Type 1 retinopathy of prematurity (ROP) in Zone I. Methods Medical records of 74 eyes of 37 infants were analysed. Only infants with Type 1 ROP in Zone I were included. Thirty-two eyes were treated with temporal-sparing laser + IVB. Both Zone I and temporal Zone II were spared to minimise potential visual field loss. Forty-two eyes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…They concluded that temporal Zone II sparing laser photocoagulation combined with IVB could be a good choice for Type 1 ROP patients to achieve complete regression while minimizing peripheral field defects. [ 12 ] The mean birth weight of the infants in our study with APROP was 1340 g. This is in accordance with similar results shown in other studies done on bigger Asian babies. [ 13 ] However, the high number of APROP cases points toward a need for improved neonatal intensive care unit practices.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that temporal Zone II sparing laser photocoagulation combined with IVB could be a good choice for Type 1 ROP patients to achieve complete regression while minimizing peripheral field defects. [ 12 ] The mean birth weight of the infants in our study with APROP was 1340 g. This is in accordance with similar results shown in other studies done on bigger Asian babies. [ 13 ] However, the high number of APROP cases points toward a need for improved neonatal intensive care unit practices.…”
Section: Discussionsupporting
confidence: 92%
“…In their study, Seo et al found no neurodevelopmental delay in the IVB and laser combination therapy group in the long term [48].…”
Section: Discussionmentioning
confidence: 78%